Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Daya Saing Lembaga Pendidikan Dasar Islam - Nur Awalliyah , Adhisti; Hadiati, Eti; Murtadho, Ali; Praja Tuala, Riyuzen (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The competition among basic educational institutions has become increasingly complex, driven by growing societal expectations for high-quality academic, character-based, and Islamic value-oriented education. This study aims to analyze school leadership strategies in enhancing the competitiveness of Islamic basic education institutions through value-based strategic management approaches. This research employed a qualitative descriptive method, collecting data through in-depth interviews, participatory observation, and documentation. Data were analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the principal adopted competitive strategies based on Michael E. Porter's theory: cost leadership, differentiation, and focus. The cost leadership strategy involved financial efficiency, external collaboration, and internal reinforcement. Differentiation was realized through unique Islamic programs, Qur'an memorization, and academic excellence. The focus strategy was implemented by targeting urban Muslim families and strengthening Islamic values in school culture. The implications of these strategies include increased student enrollment, academic achievements, and public trust in Islamic education institutions.